Enhancing Learners Autonomy: Effects of an English Camp Program - Reza Anggriyashati Adara; Irnie Victorynie; Welliam Hamer; Nur Azmi Rohimajaya (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Immersing learners in English can be a strategy to improve their autonomy in in English as a foreign language (EFL) learning. The objective of the present study is to analyze the improvement in factors related to learnersÔÇÖ autonomy after the English camp, one of types of language immersion programs. This study used a convenience sampling method. The participants consisted of thirty high school students. Therefore, the present study employed a quantitative research design by distributing a set of questionnaires before and after an-eight-day English camp program. The results suggest that the most salient factor that improves after the treatment is ÔÇÿimportant strategiesÔÇÖ┬á (m=3.6 to m=3.75) while factors related ÔÇÿthe learnersÔÇÖ sense of self-efficacyÔÇÖ (m=3.75 to m=3.91) and ÔÇÿthe role of teacherÔÇÖ (m=3.47 to m=3.5) do not suggest a drastic increase. In contrast, the items related to ÔÇÿthe role of the feedbackÔÇÖ (m=3.77 to m=3.58) show a decline. In this sense, the participants seem able to employ various important strategies to advance their language learning progress and improve their confidence while finding the roles of feedback they obtained during the program lessened. The results of this study imply the needs to provide comprehensible inputs to the students so that they can enhance their autonomy. The next study should involve the investigation of the effects of comprehensible inputs in an English camp toward learnersÔÇÖ autonomy.